A Lifecycle-Centric Hardware-in-the-Loop Validation Framework for Continuous Verification of Software-Defined Automotive Chassis and Powertrain Systems - Sana Fatima (International Journal of Intelligent Systems and Applications in Engineering, 2026)
The transition to software-defined vehicle (SDV) architectures has fundamentally altered the validation challenge for automotive chassis and powertrain embedded control systems. In traditional development cycles, validation is a pre-deployment activity: software is verified against a fixed functional specification before release, and the system is assumed stable thereafter. Software-defined vehicles dissolve this assumption entirely. Over-the-air (OTA) software updates, continuous calibration adjustments, and feature extensions delivered post-deployment create a time-varying system model in which the behavioral correctness of chassis and powertrain controllers must be re-established after every change. Existing Hardware-in-the-Loop (HIL) validation practices, designed around pre-deployment milestone verification, are structurally inadequate for this continuous, lifecycle-spanning verification demand. This paper proposes a lifecycle-centric HIL validation framework that extends HIL-based verification across development, deployment, and post-deployment phases through three integrated mechanisms: automated validation pipelines that execute HIL regression suites within 24 hours of each software update, digital twin feedback loops that continuously enrich the HIL scenario library from field-collected operational data, and embedded functional safety validation that evaluates diagnostic coverage and fault detection latency against ISO 26262 requirements after each update cycle. The framework is evaluated across 180 software update regression cycles spanning six months of simulated post-deployment operation on a dSPACE SCALEXIO platform. Key results include: a first-pass HIL success rate of 73.1%, a mean validation turnaround time of 19.4 hours, a diagnostic coverage of 91.3%, a fault detection latency of 44 ms, and a regression escape rate of 0.8%. These results demonstrate that lifecycle-centric HIL validation provides the continuous assurance capability that software-defined automotive architectures require.